Corporate Social Responsibility, Corporate Governance, Firm Size and Financial Performance of Companies in Indonesia - Yenny Wati; Fry Melda Saragih; Yusrizal Yusrizal; Yerisma Welly; Debi Eka Putri (Jurnal Ecogen, 2023)
Financial performance is critical to the company's survival. One of the goals of forming a corporation is to maximize its worth, as evidenced by the performance of its financial accounts. Investors can make decisions about a company's investing activities by measuring financial performance. As a result, investors will expect corporations to provide high-quality financial performance reports. This study sought to investigate the impact of corporate social responsibility, corporate governance, and firm size on financial performance. This study makes use of secondary data from manufacturing firms registered on IDX (Indonesia Stock Exchange) between 2017 and 2022. Purposive sampling was used to select the sample that met particular requirements. In this research, the data was examined using multiple linear regression tests. According to the findings of this research, CSR (corporate social responsibility), CG (corporate governance), and size of the firm are all having significant positive impacts on financial performance. Because of the importance of CSR (Corporate Social Responsibility) and GCG (Good Corporate Governance) in firms for the future, investors should pay attention to components of CSR (Corporate Social Responsibility) and GCG (Good Corporate Governance) in financial reports, which can be utilized as a consideration in investing